Authentic or comfortable? What tourists want in the destination - He, Linsi; Timothy, Dallen J. (Frontiers in Sustainable Tourism, 2024)
Authenticity is a popular research topic in tourism studies and is an important destination attribute that influences tourists and their decision-making. However, some studies have shown that tourists do not always seek authentic experiences and places. The purpose of this paper is to surmise why this might be the case. We employ Maslow's hierarchy of needs to articulate that pursuing authenticity represents a high-order need, and most tourists seek a balance between pursuing authenticity and lower-order needs, especially comfort. Based on level of comfort and perceived authenticity, four quadrants are presented, representing “desirable (comforting) authenticity,” “discomforting authenticity,” “discomforting-inauthenticity,” and “comforting-inauthenticity.” The paper argues that the optimal tourism product is the one associated with “desired authenticity.” Practical implications, limitations and future research suggestions are provided.